Warning assessment: Information design contributions to the evaluation of communication efficacy of front of packaging nutrition labelling - Urquizar Rojas, Carlos Felipe; Galvão Spinillo, Carla (InfoDesign, 2021)
In the context of nutrition and public health, researchers have evaluated the effectiveness of front of package nutrition warning labels to guide regulatory policies. Their studies little have focused on graphic aspects of warning design that may influence attention, legibility, understanding and processing of information by consumers. Considering this, a meta-analysis of 11 articles selected from the systematic review of the call No. 17/2017 CNPq/ANVISA is presented here. The meta-analysis aimed to (a) identify tests used in studies that evaluated the communication efficacy of front of package nutrition warning labels, and (b) to establish their possible relations to the stages of the communication human information processing model for warnings (C-HIP Model). It includes the following phases: attention switch, attention maintenance, comprehension and memory, attitudes and beliefs, motivation and behavior. The results indicated: predominance of tests on behavioral intentions and healthfulness perception; focus on the final phases of the C-HIP Model and less attention to aspects about information design in warning labels. It is concluded that there are gaps in nutrition research area about factors associated to the design and processing of warning information, thus demanding future investigations.